Penerapan Model Pembelajaran Round Club untuk Merencanakan Pembelajaran di Kelas V MI Nurul Iman - Desy Susanti (At-Tajdid : Journal of Islamic Studies, 2023)
The application of the Round Club Learning Model to student learning planning is the main objective of this research. This research is a classroom action research (PTK) with a background of low learning Indonesian for fifth grade students. In the 2022-2023 school year, the study participants were teachers and fifth grade students, with a total of 12 boys and 13 girls. So that a total of 26 students. In addition, the purpose of this research is to apply the Learning Model to plan student learning. The sample used in this study was obtained by observation and test techniques. Prior to the activity, 14 students completed the action or achieved 50.00% student completeness, but the Cycle I score of 18 students was 69.23%. After taking corrective action, in Cycle II it was found that the level of completeness of students was 20 students, or the level of completeness of students was 92.31%. This means that student learning outcomes reach 75% of the specified KKM or 75. It can be concluded that the application of the Round Club Learning Model improves Indonesian learning outcomes for class V MI Nurul Iman.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//